Neurogenomics contribution to neurodegenerative Diseases - Adeleye, Olufunto Omodele; Olorunlowu, Darasimi Racheal; Yusuf, Joshua Ayodele; Opoola, Elizabeth Kehinde; Akanbi, Stephen Tunmise; Akindokun, Segun Samson (Nepal Journal of Neuroscience, 2024)
Introduction: Neurodegenerative diseases are a group of complex disorders that progressively impair the structure and function of the nervous system, resulting in debilitating symptoms and reduced quality of life for affected individuals. Over the past few decades, advances in the field of genomics have revolutionized our understanding of the underlying molecular mechanisms driving these disorders. Neurogenomics, the intersection of neuroscience and genomics, has emerged as a crucial discipline in unraveling the genetic and molecular underpinnings of neurodegenerative diseases. Neurogenomics focuses on deciphering the genetic variations that contribute to the susceptibility and progression of neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis (ALS), and Huntington’s disease. Advances in DNA sequencing technologies have enabled researchers to identify specific genetic mutations and variations that are associated with increased disease risk. By studying the genetic mutations involved in neurodegenerative diseases, neurogenomics has provided valuable insights into the underlying disease mechanisms. These insights have led to a deeper understanding of protein aggregation, mitochondrial dysfunction, inflammation, and other cellular processes implicated in disease progression. By harnessing the power of neurogenomics through further studies, researchers and clinicians are moving closer to the goal of effectively preventing, diagnosing, and treating neurodegenerative diseases, thus offering hope to millions of individuals affected by these challenging conditions. Conclusion: Neurogenomics has emerged as a pivotal field in unraveling the complex interplay between genetics and neurobiology in neurodegenerative diseases. By dissecting the genetic architecture, elucidating molecular mechanisms, and paving the way for targeted therapies, neurogenomics offers new avenues for understanding, diagnosing, and ultimately treating these disorders.